Prevalence and factors associated with anemia among HIV-infected women in sub-saharan Africa: a multilevel analysis of 18 countries - Werkneh Melkie Tilahun; Zenebe Abebe Gebreegziabher; Habtamu Geremew; Mulat Belay Simegn (BMC, 2024)
Abstract Background Despite the intended 50% reduction in anemia in women of reproductive age, this tendency has only worsened. Even though iron deficiency is the most prevalent cause of anemia, anemia and chronic illnesses like HIV are closely associated; in fact, 48.6% of people living with HIV who were 15 years of age or older had anemia. However, the burden of anemia among HIV-positive women in sub-Saharan African (SSA) countries is not well documented. Therefore, the goal of our research was to investigate anemia and the factors that are linked to it in SSA women who had HIV infections. Methods A cross-sectional study was conducted using demographic and health survey datasets from 18 SSA countries. A total of 7823 weighted samples were included. STATA version 16 software was used for analysis. A multilevel logistic regression model was fitted. An adjusted odds ratio with a 95% CI and a p-value < 0.05 was used to declare significantly associated factors. Result The overall prevalence of anemia was found to be 45.1% [95% CI: 43.97-46.18%]. Of those 5.05%, 37.97%, and 56.97% were severely, moderately, and mildly anemic, respectively. Education level of primary [AOR = 0.74, 95% CI: 0.62, 0.89], secondary [AOR = 0.81, 95% CI: 0.68, 0.98], and higher [AOR = 0.74, 95% CI: 0.55, 0.99], as well as current contraceptive use [AOR = 0.74, 95% CI: 0.63, 0.87] were negatively associated with anemia. While pregnancy [AOR = 1.51, 95% CI: 1.17, 1.94], breast feeding [AOR = 1.38, 95% CI: 1.17, 1.64], health insurance [AOR = 1.50, 95% CI: 1.25, 1.80], and menstruation within six weeks prior to data collection [AOR = 1.36, 95% CI: 1.20, 1.54] had a significant positive relation with anemia among HIV-infected women in SSA countries. Conclusion Anemia is a serious public health problem among HIV-infected women in SSA countries. Pregnancy, breast feeding, health insurance, and menstruation within six weeks prior to data collection were significant risk factors. On the other education and current contraceptive use were significant protective factors for anemia among HIV-infected women in SSA countries. Therefore, strategies aimed at early identification of anemia may lead to an improvement in the health of HIV-infected women.